Contemporary gender transformations in South Asia : transcending the archetype of womanhood - Haque, Reazul (Emerald Publishing Limited, 2025)
In South Asia, traditional views of gender, especially womanhood, are evolving from static roles to dynamic identities shaped by social, cultural, and technological shifts. This nuanced understanding of womanhood goes beyond past frameworks focused on patriarchy and traditional female-led narratives. Today, gender issues intersect with the media, state policies, and digital activism, reflecting both local and global influences on gender discourse. In Contemporary Gender Transformations in South Asia: Transcending the Archetype of Womanhood, Reazul Haque presents an insightful exploration into how modern gender expressions in South Asia resist traditional archetypes and adapt to contemporary social shifts. This work examines how gender identities in the region are not only fluid but also capable of significant cognitive transformation in response to historical and cultural influences. By analyzing the impact of state, market, religious, and media institutions on gender roles, Haque argues for an inclusive yet cautious approach, acknowledging the risks of universalizing diverse gender experiences. His study also draws on recent digital and activist movements, which challenge existing power structures, offering a comprehensive view of how gender dynamics in South Asia are actively reimagined and redefined. Providing a fresh perspective for scholars, policymakers, and those interested in gender studies and South Asian cultural studies, this volume asks readers to consider the active roles individuals and institutions play in reshaping gender expression today.